Balloon-occluded versus conventional transarterial chemoembolization for the treatment of early to intermediate stage hepatocellular carcinoma: a meta-analysis and trial sequential analysis - Jiaxi Liu; Weiwei Wang; Huan Zhai; Yanan Ma; Qiwen You; Haibo Shao (BMC Cancer)
Abstract Background We performed a meta-analysis and trial sequential analysis (TSA) to compare the therapeutic efficacy and adverse events (AEs) of balloon-occluded transarterial chemoembolization (B-TACE) with conventional transarterial chemoembolization (cTACE) in treating early-to-intermediate-stage hepatocellular carcinoma (HCC). Methods We systematically searched PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang databases for studies comparing B-TACE and cTACE in the treatment of HCC. The outcomes included the complete response (CR) rate, objective response rate (ORR), lipiodol consumption, and adverse events (AEs). Depending on the heterogeneity assessment, either a fixed-effects or random-effects model was utilized, followed by a meta-analysis using Review Manager 5.3. Additionally, a TSA was conducted to assess the adequacy of the sample size. Results Five studies including a total of 1166 patients were analyzed. This meta-analysis revealed that compared with cTACE, B-TACE significantly improved the CR rate (risk ratio [RR] = 1.21, 95% confidence interval [CI] 1.04–1.42, p = 0.02) and the ORR (RR = 1.23, 95% CI 1.09–1.38, p = 0.0006). These findings were validated using TSA, which did not require a larger information size. The TSA results indicated that B-TACE consumed more lipiodol than cTACE, potentially leading to more satisfactory embolization efficacy. In terms of AEs, only post-embolization syndrome was found to occur more frequently in patients treated with B-TACE than in those treated with cTACE (RR = 1.30, 95% CI 1.01–1.68, p = 0.04). However, the TSA suggested that additional cases are necessary to confirm this difference. Conclusions B-TACE consumed more lipiodol and demonstrated superior effects on the CR rate and ORR compared to cTACE in the treatment of HCC. Importantly, this improvement in efficacy did not correspond to a significant increase in AEs. Based on these findings, it is recommended that well-designed, large-scale randomized controlled trials be conducted to further validate and expand upon these results. Trial registration This study was registered in the international prospective register of systematic reviews PROSPERO (registration No: CRD42023489055).